2021
DOI: 10.1007/s11897-021-00517-y
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Cancer in the HF Population: Epidemiology, Pathophysiology, and Clinical Management

Abstract: Purpose of Review Oncological treatments are known to induce cardiac toxicity, but the impact of new-onset cancer in patients with pre-existing HF remains unknown. This review focuses on the epidemiology, pathophysiological mechanisms, and clinical implications of HF patients who develop malignancies. Recent Findings Novel findings suggest that HF and cancer, beside common risk factors, are deeply linked by shared pathophysiological mechanisms. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Yusuf et al showed that less than 50% of patients with acute coronary syndrome and cancer received applicable therapy [ 25 ]. It may be that comorbidities, cancer status, and cancer therapy affected the physician’s decision [ 6 ].Cancer patients were excluded from HF clinical trials with ACE-I, beta-blockers, mineralocorticoid receptors, and statins and we do not have data on their efficacy in the cancer HF population [ 26 ]. Although such a therapy saves lives in the general HF population, prospective trials to prove the benefits of this therapy in cancer patients would be unethical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yusuf et al showed that less than 50% of patients with acute coronary syndrome and cancer received applicable therapy [ 25 ]. It may be that comorbidities, cancer status, and cancer therapy affected the physician’s decision [ 6 ].Cancer patients were excluded from HF clinical trials with ACE-I, beta-blockers, mineralocorticoid receptors, and statins and we do not have data on their efficacy in the cancer HF population [ 26 ]. Although such a therapy saves lives in the general HF population, prospective trials to prove the benefits of this therapy in cancer patients would be unethical.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, patients diagnosed with cancer have a higher prevalence of pre-existing CVD than the general population, and the type and prevalence of CVD varies significantly by cancer aetiology [ 2 ]. On the other hand, patients with heart failure (HF) are at a greater risk of cancer occurrence, which increases over time [ 3 , 4 , 5 , 6 ]. The incidence of cancer in established HF has been estimated to be in the range of 18.9–33.7 per 1000 person-years by retrospective analyses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the associations between established tumor biomarkers and indices of HF severity, along with their independent prognostic value for the HF outcomes of these biomarkers, and between classic cardiovascular biomarkers and cancer patient prognosis, may suggest the presence of dysregulated pathophysiologic pathways common to both cancer and cardiovascular diseases [61]. As already mentioned, the existent correlation between these two conditions is well recognized in the scientific literature and, remarkably, it has been highlighted that cancer and cardiovascular disease share many risk factors, as well as a common underlying inflammatory condition [57][58][59]61,62,73]. Of note, this chronic phlogistic state has been also observed in clinical practice and reported in the literature, with the help of serum inflammatory markers such as C-reactive protein (CRP) and proinflammatory cytokines such as interleukin 6 (IL-6) in both cancer and HF [19,[74][75][76][77][78].…”
Section: Cardiovascular Biomarkers In Cancer Patients Vs Tumor Biomar...mentioning
confidence: 93%
“…In fact, it has emerged that patients affected by HF present with high serum levels in several biomarkers presumed to be tumor-related, such as CA19-9, CA125 and human epididymis protein 4 (HE4) [51][52][53][54][55][56]. The possible interconnections between HF and cancer extend far beyond HF being a manifestation of CTRCD, and they have been deeply investigated in the last few decades [57][58][59][60][61][62][63]. Interestingly, an analysis of 2079 patients affected by HF in the BIOSTAT-CHF cohort [64] proved that the blood levels of five out of the six tumor biomarkers that they investigated (CA125, CA15-3, CA19-9, CEA and CYFRA 21-1) were significantly correlated with all-cause mortality, while CA125 also showed a strong correlation with HF hospitalization risk, and CYFRA 21-1 had equivalent predictive utility for all-cause mortality when compared with NTproBNP levels [51].…”
Section: Cardiovascular Biomarkers In Cancer Patients Vs Tumor Biomar...mentioning
confidence: 99%
“…Heart failure (HF) and cancer are currently the leading causes of death worldwide, with an increase incidence with age [1]. It has been proposed that cardiovascular disease (CVD) and cancer share multiple pathophysiological mechanisms, and their association is very common [2][3][4]. The cardiotoxic effects of antineoplastic agents lead to the development of the specialty of cardio-oncology to improve care of patients and avoid the development of HF that can appear years after treatment is completed.…”
Section: Introductionmentioning
confidence: 99%